2005
DOI: 10.1017/s109285290002277x
|View full text |Cite
|
Sign up to set email alerts
|

Can Telepsychiatry Replace In-Person Psychiatric Assessments? A Review and Meta-Analysis of Comparison Studies

Abstract: Objective: The authors conducted a review and meta-analysis of the literature comparing telepsychiatry with “in-person” psychiatric assessments.Method: Approximately 380 studies on telepsychiatry published between 1956 and 2002 were identified using MEDLINE, PsycINFO, and cross-referenced bibliographies. Of these, 14 studies with an N>10 compared telepsychiatry with in-person psychiatry (I-P) using objective assessment instruments or satisfaction instruments. Three of these studies compared high bandwidth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 56 publications
2
116
1
7
Order By: Relevance
“…[48][49]51 Ten systematic reviews were selected (QS ≥22) for detailed extraction of findings and evidence based recommendations (Table IV). 23,[26][27][28][38][39][54][55][56][57] One of these was a policy document which provided detailed grading of evidence-based recommendations. 38 Two of these systematic reviews were non-effectiveness reviews included to provide synthesised information on utilization and cost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49]51 Ten systematic reviews were selected (QS ≥22) for detailed extraction of findings and evidence based recommendations (Table IV). 23,[26][27][28][38][39][54][55][56][57] One of these was a policy document which provided detailed grading of evidence-based recommendations. 38 Two of these systematic reviews were non-effectiveness reviews included to provide synthesised information on utilization and cost.…”
Section: Resultsmentioning
confidence: 99%
“…The recommendations extracted from the different studies in the systematic reviews were subjected to evidence and video application grading based on the clinical coding methodology developed by the American Telemedicine Association cited in Grady (2011) (Table II). 38 As Hyler (2005) found that bandwidth was a confounder in evaluation studies 39 , bandwidth was included in the video application classification and each study used in a review was classified by letters (HD -LB) according to bandwidth and resolution. The recommendations from the studies were assigned evidence grading by numbers (1-3), equivalent to standard recommendations ratings A-C, for research quality confidence.…”
Section: Review Processmentioning
confidence: 99%
“…Latency is reduced at higher bandwidths. Even though there is evidence that suggests that there is a slight superiority of Internet Protocol (IP) connectivity over ISDN connectivity 29 , there is acceptance that 128Kbps is adequate for some clinical applications. 30 Planning Most hospitals in the province connect at 128Kbps for videoconferencing using ISDN lines.…”
Section: Bandwidth Testing For Clinical Outreach Telepsychiatry Servicesmentioning
confidence: 99%
“…Entre ellos se destacan trabajos: (a) que demuestran la satisfacción del terapeuta y del usuario con la nueva tecnología (Giles, 2001;Skinner y Latchford, 2006;Urness, Wass, Gordon, Tian, y Bulger, 2006); (b) que comparan la efectividad de estas herramientas respecto a listas de espera e intervenciones tradicionales (Andersson, 2009); análisis de costos (O'Reilly, et al, 2007); y (c) de meta-análisis o revisión (Hyler, Gangure, y Batchelder, 2005;Pelechano, 2007;Spek, et supervisiones (Kaltenthaler, Parry, y Beverley, 2004). La ciber-terapia también suele ser denominada e-terapia, consulta online, cyber-terapia, terapia virtual, terapia online, consejo web, tele-salud conductual, tele-psiquiatría, consejería a distancia, o e-terapia conductual (Caldwell y Gottesman, 1990;Carlbring y Andersson, 2006;Giles, 2001;Grohol, 1999;Kaltenthaler, et al, 2004;Valero, 2003), defi niciones que expresan su divergencia conceptual ya que cada una de ellas aporta pequeños matices.…”
Section: Internet Y Psicología Clínica: Revisión De Las Ciber-terapiasunclassified